Political Aspects of the Drama “Hlapci” - Jasmina Šuler-Galos; Grzegorz Kołodziej (Slavia Meridionalis, 2024)
Political Aspects of the Drama Hlapci Contemporary discussions of the deep ideological divide in Slovenian society encompass many arguments that hark back to the cultural struggle waged at the turn of the 20th century. The word ‘farmhand’ was first used metaphorically by Ivan Cankar in the play Hlapci [Farmhands] and remains one of the most frequently used concepts in this debate. In the article, it is treated as a nodal point which connects and stabilises elements of the Slovenian leftist discourse from the early 20th century to the present day.   Polityczne aspekty dramatu Hlapci Współczesne dyskusje dotyczące głębokiego podziału ideologicznego społeczeństwa słoweńskiego zawierają wiele argumentów używanych w wojnie kulturowej toczonej na przełomie XIX i XX wieku. Słowo parobek, w znaczeniu metaforycznym po raz pierwszy użyte przez Ivana Cankara w roku 1910 w dramacie Hlapci [Parobki], należy w tej dyskusji do najczęściej używanych pojęć. W artykule jest traktowane jako punkt węzłowy słoweńskiego lewicowego dyskursu od początku XX wieku do dziś.